Resource Allocation with Adaptive Spread Spectrum OFDM Using 2D Spreading for Power Line Communications. (26th June 2007) - Baudais Baudais, Jean-Yves Jean-Yves; Crussière Crussière, Matthieu Matthieu
Abstract : Bit-loading techniques based on orthogonal frequency division mutiplexing (OFDM) are frequently used over wireline channels. In the power line context, channel state information can reasonably be obtained at both transmitter and receiver sides, and adaptive loading can advantageously be carried out. In this paper, we propose to apply loading principles to an spread spectrum OFDM (SS-OFDM) waveform which is a multicarrier system using 2D spreading in the time and frequency domains. The presented algorithm handles the subcarriers, spreading codes, bits and energies assignment in order to maximize the data rate and the range of the communication system. The optimization is realized at a target symbol error rate and under spectral mask constraint as usually imposed. The analytical study shows that the merging principle realized by the spreading code improves the rate and the range of the discrete multitone (DMT) system in single and multiuser contexts. Simulations have been run over measured power line communication (PLC) channel responses and highlight that the proposed system is all the more interesting than the received signal-to-noise ratio (SNR) is low.